The digital notion of the citizen-centred media ecosystem. (1st September 2018) - Raycheva, Lilia
The technology breakthrough in fields such as artificial intelligence, robotics, the Internet of Things, 3D printing, etc. pose significant challenges to the contemporary media (traditional and social) and information ecosystem. Using PEST analysis, this article examines the political, economic, social and technological aspects of the demographic and literacy trends and disruptions in the media and communication ecosystem (based on digital practices in Bulgaria). The article concentrates on the political and regulatory commitment to fundamental values when developing new trajectories in the domains of technology, business and governance; the transformation of the business models for meeting customers' expectations for personalized interaction at all points of their consumer experience; the scaling up of citizen-centred technologies as phenomenal opportunities for human progress, which also create serious societal challenges; and the impact of technological developments on society.